2015
DOI: 10.1038/onc.2014.473
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic p27 promotes epithelial–mesenchymal transition and tumor metastasis via STAT3-mediated Twist1 upregulation

Abstract: p27 restrains normal cell growth, but PI3K-dependent C-terminal phosphorylation of p27 at threonine 157 (T157) and T198 promotes cancer cell invasion. Here, we describe an oncogenic feedforward loop in which p27pT157pT198 binds Janus kinase 2 (JAK2) promoting STAT3 (signal transducer and activator of transcription 3) recruitment and activation. STAT3 induces TWIST1 to drive a p27-dependent epithelial–mesenchymal transition (EMT) and further activates AKT contributing to acquisition and maintenance of metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 59 publications
6
104
0
Order By: Relevance
“…These results suggest that the CypB/STAT3/miR-520d-5p feedback loop is also present in clinical samples. Recently, researchers found that the transcription of TWIST1, a miR-520d-5p functional target (34), was increased by the activation of STAT3 and its binding to the TWIST1 promoter (47), suggesting another potential feedback loop that may regulate metastasis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the CypB/STAT3/miR-520d-5p feedback loop is also present in clinical samples. Recently, researchers found that the transcription of TWIST1, a miR-520d-5p functional target (34), was increased by the activation of STAT3 and its binding to the TWIST1 promoter (47), suggesting another potential feedback loop that may regulate metastasis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell mesenchymalization takes place when epithelial cancer cells lose their polarity, cell-to-cell contacts, and expression of epithelial proteins, including E-cadherin, ZO-1, and cytokeratins, while gaining the expression of proteins normally found in mesenchymal cells, such as fibronectin and vimentin (34,35). Mesenchymalization and the molecular drivers of the process, including the transcription factors Snail, Slug, Twist, and brachyury, have been linked to advanced tumor stage (36)(37)(38), presence of metastases (39), and poor prognosis in numerous cancer types (40)(41)(42). Additionally, mesenchymalization has been associated with resistance to anticancer therapies, including chemotherapy (43,44), small-molecule-targeted therapies (45,46), and to lysis by immune effector cells (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Jak2/STAT3 signaling has been shown to have a pivotal role in the epithelial-mesenchymal transition (EMT) to cancer cells, 16 and the importance of Jak2/STAT3 signaling in bladder cancer progression has been implicated. Zhao et al 27 showed that activation of Jak2/STAT3 in bladder cancer cells drove EMT and tumor invasion. Joung et al 28 reported that AG490, a Jak2 inhibitor, could inhibit bladder cancer cell viability and cell migration, accompanied by reduction of STAT3 signaling.…”
Section: Discussionmentioning
confidence: 99%